2014
DOI: 10.17681/hsp.26416
|View full text |Cite
|
Sign up to set email alerts
|

Duygusal Zekâ ve Ebelik

Abstract: Duygusal Zekâ ve Ebelik* Emotional Intelligence and MidwiferyÖzet Duygusal zekâ, bireylerin öncelikle kendi duygularını anlamalarını ve yönetebilmelerini sağlayan, bunun yanında başkalarının duygularını anlayabilme, empati kurabilme, motivasyonlarını arttırma ve özgüven duygularını geliştirme olanağı tanıyan bir kavramdır. Duygusal zekâ, ebelik uygulamalarında profesyonel ilişkilerin ve karmaşık olaylarda farklı bakış açılarının gelişmesine yardım edebilir. Ebeler, gebelere empatik bir tutumla yaklaştıklarında… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…The enhancement of the quality of the practices related to the profession that offer assistance and care to people will be possible through effective communication between people who provide care and who are provided care. 11,12,13 Effective interpersonal relationships, aiding and counseling skills are the skills that a midwife needs to acquire and form the preconditions for good quality midwifery care. 13 When the communication skills of the students studying in the midwifery and nursing departments are evaluated, it has been determined that their communication skills are good/high.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The enhancement of the quality of the practices related to the profession that offer assistance and care to people will be possible through effective communication between people who provide care and who are provided care. 11,12,13 Effective interpersonal relationships, aiding and counseling skills are the skills that a midwife needs to acquire and form the preconditions for good quality midwifery care. 13 When the communication skills of the students studying in the midwifery and nursing departments are evaluated, it has been determined that their communication skills are good/high.…”
Section: Discussionmentioning
confidence: 99%
“…11,12,13 Effective interpersonal relationships, aiding and counseling skills are the skills that a midwife needs to acquire and form the preconditions for good quality midwifery care. 13 When the communication skills of the students studying in the midwifery and nursing departments are evaluated, it has been determined that their communication skills are good/high. 14,15,16,1 In a study in which the emotional intelligence abilities of executive nurses were examined, it was found that scores of the nurses were above average and they received high scores from social responsibility, empathy and problem solving subscales.21 In the study of Kuzu ve Eker's (2010) in which emotional intelligence and communication skills of nursing students and other university students were evaluated, communication skills and emotional intelligence average scores of nursing students were signifi cantly higher than the average scores of the other university students.14 In some studies conducted on nursing students, emotional intelligence average scores of the students were found to be at moderate level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations